Panel Summary: Enhancing Access to Patient-centred Primary Care in Ontario - Waddell, K; Wilson, MG (My University, 2016)
A summary of what was learned from a citizen panel that addressed problems related to patient-centred primary care in Ontario, options for addressing these problems, key implementation considerations, and next steps for enhancing access to patient-centred primary care in Ontario.
Keywords: enhancing; access; patient-centred; primary; care; Ontario